Neutron Irradiation on SS316 Material for Radioactive Endovascular Stent Production - Awaludin, Rohadi; Abidin, Abidin; Sriyono, Sriyono (UI Scholars Hub, 2008)
Neutron Irradiation on SS316 Material for Radioactive Endovascular Stent Production. It was reported that restenosis could be prevented by radioactive endovascular stent. SS316 material of endovascular stent has been irradiated at pneumatic rabbit system of G.A. Siwabessy reactor for 5 minutes for producing radioactive stent by neutron activation. After 10 days of decay, the irradiated SS316 was measured by gamma spectrometer. The radioisotopes of 51Cr, 59Fe and 60Co were detected in the irradiated SS316 with radioactivity of 5990, 107 and 109 Bq/mg respectively. The Calculation results showed that radioisotopes of 51Cr, 59Fe and 55Fe were produced by neutron activation. The radioactivity of 51Cr, 59Fe and 55Fe were 6051, 70 and 110 Bq/mg respectively. In the irradiated materials, the 55Fe was not detected because the radioisotope emitted radiation with very low energy (5.9 keV). It is considered that radioisotope of 60Co was produced from cobalt impurity in the SS316.